Respuesta :
Answer:
Hi there!
Given equation :-
[tex]\:\mathsf{a^2\:-\:5a\:+\:6\:=\:0}[/tex]
Now
=> By splitting the middle term
=> [tex]\:\mathsf{a^2\:-\:2a\:-\:3a\:+\:6\:=\:0}[/tex]
=> [tex]\:\mathsf{a(a\:-\:2)\:-\:3(a\:-\:2)\:=\:0}[/tex]
=> [tex]\:\mathsf{(a\:-\:2)\:-\:(a\:-\:3)\:=\:0}[/tex]
We get ,
=> [tex]\:\sf{a\:=\:2\: and\: a\:=\:3}[/tex]
[tex]\:\mathsf{Hope\:this\:helps\:you!\::)}[/tex]
Thank you!
Answer:
[tex]a = 3 \: \: \: and \: \: a = 2[/tex]
Step-by-step explanation:
⬇
[tex]a^{2} - 3a - 2a + 6 = 0[/tex]
⬇
[tex]a \: (a - 3) \: \: (a - 2)[/tex]
⬇
[tex]{}\ a - 3 = 0 \\ a = 2{}[/tex]